2021
DOI: 10.4103/jmp.jmp_2_20
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multiple-Tube Phantom

Abstract: Background: Native T1 relaxation time (T10) presents an important prerequisite to reliably quantify pharmacokinetic parameter like Ktrans (volume transfer constant). Native T1 value can be varied because of the inhomogeneity in the breast coil, thus influencing the Ktrans measurement. Purpose: The current study aims to design and use a phantom with multiple tubes for both breast cuffs to assess native T1 inhomogeneity across the dedicated molecular magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The acquisition of phantom image was done using DFA method to derive correction factor for T 1 value at each spatial location. [ 28 ] The correction factor so obtained was then applied to Native T 10 values of breast lesions of 39 patients that was spatially synchronized with the lesion. The patients were selected consecutively from the database between 2018 and 2021 with a mean age of 50 years (31–77 years) having a total 51 lesions who had undergone breast PET/MRI study as part of their diagnostic/staging workup with proven cancer on histopathology before or done subsequently after their PET/MRI scan.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acquisition of phantom image was done using DFA method to derive correction factor for T 1 value at each spatial location. [ 28 ] The correction factor so obtained was then applied to Native T 10 values of breast lesions of 39 patients that was spatially synchronized with the lesion. The patients were selected consecutively from the database between 2018 and 2021 with a mean age of 50 years (31–77 years) having a total 51 lesions who had undergone breast PET/MRI study as part of their diagnostic/staging workup with proven cancer on histopathology before or done subsequently after their PET/MRI scan.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…Later on, Negi et al . [ 28 ] adopted an in vitro reference method to normalize T 1 distribution using an in-house designed multiple tube phantom placed within the breast coil cuffs and T 1 was calculated using DFA protocol. The T 1 values were normalized in the molecular magnetic resonance (mMR) breast coil-cuff by applying correction factors derived for each spatial location and observed that before the application of correction factors, T 1 distribution was inhomogeneous in different parts of each breast coil cuff as well as between the left and right coil cuff.…”
Section: Introductionmentioning
confidence: 99%